PREDIKTOR KINERJA KARYAWAN LE JARDIN BOUTIQUE VILLA SEMINYAK - Firmansyah, Dedy; Sriathi, A.A. Ayu (E-Jurnal Manajemen, 2016)
Tourism in Bali as a pillar into economic power. Companies that want sustainable, must put the human resources that are reliable and have good performance as human capital. The purpose of this study was to determine the effect of transactional leadership, organizational citizenship behavior (OCB), professional commitment and significant positive effect on employee performance at Le Jardin Boutique Villa Seminyak.Choosing Le Jardin Boutique Villa Seminyak as a location with a total sample of 40 respondents. Through multiple linear regression analysis technique.Results of the analysis proves transactional leadership, organizational citizenship behavior and professional commitment and significant positive effect on employee performance with R2 values of 85.1%, while the remaining 14.9% is influenced by other factors.
Keywords: transactional leadership; organizational citezenship behavior (ocb); professional commitment and performance